Enkele beginselen van de persoonlijke, professionele en interculturele ontwikkeling van toekomstige vertalers: (Niet alleen voor neerlandici) - Milošovičová, Petra (Acta Neerlandica, 2024)
Some principles of intercultural personal development for future translators (not only Dutch translators). This paper points out the necessary hard and soft skills of future translators and interpreters with regard to their intercultural competences. The issue has been widely discussed around the world, but the wide range of problems needs to be updated in each country, for each language pair. For students of Dutch Studies, the fact that Dutch as a pluricentric language often has terminological variants and pseudo-synonyms adds to this. In any case, this should also be conveyed didactically and thus sensitize the students in this respect as well.